Two new species of Eupariini Schmidt, 1910 (Coleoptera: Scarabaeidae: Aphodiinae) from Indonesia - Minkina, Łukasz; Jákl, Stanislav (Zootaxa, 2024)
Two new species of Eupariini Schmidt, 1910 are described and illustrated: Airapus malaitaensis Minkina & Jákl, new species from Solomon Islands (Malaita Island) and Saprosites mapiaensis Minkina & Jákl, new species from Indonesia (New Guinea). New species are compared with their close relatives, Airapus burrundieae Stebnicka & Howden, 1996 and Saprosites crockerensis Stebnicka, 1991, respectively.